1994
DOI: 10.1523/jneurosci.14-06-03775.1994
|View full text |Cite
|
Sign up to set email alerts
|

Motor sequence learning: a study with positron emission tomography

Abstract: We have used positron emission tomography to study the functional anatomy of motor sequence learning. Subjects learned sequences of keypresses by trial and error using auditory feedback. They were scanned with eyes closed under three conditions: at rest, while performing a sequence that was practiced before scanning until overlearned, and while learning new sequences at the same rate of performance. Compared with rest, both sequence tasks activated the contralateral sensorimotor cortex to the same extent. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

72
600
6
10

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,044 publications
(703 citation statements)
references
References 27 publications
72
600
6
10
Order By: Relevance
“…Moreover, since the frontal and parietal inferior areas were engaged by the two tasks at the same time, these results are in agreement with the hypothesis that overlapping cerebral activity is the physiological basis for interference in the dual-task condition. This hypothesis is furthermore supported by the observation that practice is associated with a decrease in interference between two tasks, as well as decreases in prefrontal and cingulate activity and thus presumably a decrease in overlapping activation [59,92].…”
Section: Dual-task Coordinationmentioning
confidence: 70%
“…Moreover, since the frontal and parietal inferior areas were engaged by the two tasks at the same time, these results are in agreement with the hypothesis that overlapping cerebral activity is the physiological basis for interference in the dual-task condition. This hypothesis is furthermore supported by the observation that practice is associated with a decrease in interference between two tasks, as well as decreases in prefrontal and cingulate activity and thus presumably a decrease in overlapping activation [59,92].…”
Section: Dual-task Coordinationmentioning
confidence: 70%
“…The procedural system is composed of a network of several interconnected brain structures (De Renzi, 1989;Heilman et al, 1997;Hikosaka et al, 2000;Jenkins et al, 1994;Mishkin et al, 1984;Rizzolatti et al, 2000; Schacter and Tulving, 1994;Squire and Zola, 1996). Within the cerebrum, the system depends especially on structures in the left hemisphere (De Renzi, 1989;Heilman et al, 1997;Schluter et al, 2001).…”
Section: The Procedural Memory Systemmentioning
confidence: 99%
“…(For the sake of simplicity, below we also refer to the system as the "procedural system".) The system underlies aspects of rule-learning (Knowlton et al, 1996;Poldrack et al, 1999), and is particularly important for acquiring and performing skills involving sequences -whether the sequences are serial or abstract, or sensori-motor or cognitive (Aldridge and Berridge, 1998;Boecker et al, 2002;Graybiel, 1995;Jenkins et al, 1994;Saint-Cyr et al, 1988;Willingham, 1998). Acquisition of the procedures is gradual, in that learning occurs on an ongoing basis during multiple trials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Learning is INTACT PROCEDURAL MOTOR SEQUENCE LEARNING 5 demonstrated by improvement in the speed of response across trials and, more specifically, by the difference in response latency between a random block of stimuli and the repeating sequence block, indicating clearly that skill learning was sequence-specific. Neuroimaging studies have demonstrated that procedural sequence learning is supported by the basal ganglia and the cerebellum (e.g., Jenkins, Brooks, Nixon, Frackowiak, & Passingham, 1994), and the SRT paradigm has been widely used to explore memory abilities in various neurological pathologies characterized by impairments in these regions, such as Parkinson's disease (e.g., Helmuth, Mayr, & Daum, 2000). In children, the SRT task has also been used to explore procedural learning in developmental disorders (e.g., Lum et al, 2012;Vicari et al, 2005) To our knowledge, only two studies have investigated the motor difficulties of children with DCD with the SRT paradigm.…”
Section: Intact Procedural Motor Sequence Learningmentioning
confidence: 99%